Enseignant·es mexicain·es de FLE ou acteur·rice·s glottopolitiques pour la diversité linguistique ? - Moisés Abad Gervacio (Lengas)
This contribution presents the results of a study carried out among Mexican teachers of French as a foreign language as part of a doctoral research project currently being finalized. Through comprehensive semi-structured interviews, this article explores how the participants in this survey appropriate and invest in French, examining in particular their positioning with regard to linguistic diversity in the Mexican context and the persistence of linguistic inequalities.We illustrate how sociolinguistic appropriation among four teachers contributes significantly to the (de)construction of linguistic ideologies, leading to the development of various glottopolitical stances and identities. We examine how these actors in Mexican education and the promotion of French represent their trajectories, their plurilingual imaginaries and their professional practices within a glottopolitical perspective in favor of linguistic plurality.